METHODS OF RESEARCH OF ELECTRO-PHYSICAL CHARACTERISTICS OFAGGLUTINANTSANDS - D. M. Kukuj; S. L. Rovin; M. A. Saikov (Литьë и металлургия, 2004)
In the article the authors offer original methods of experimental investigation of electrophysical characteristics °f different agglutinant sands, used in foundry. Analysis of these characteristics, knowledge of their interconnections with composition of agglutinant sands allows to develop the most effective and safe systems of quality control and management of the mix preparation and forming processes.